CARDIAC MAGNETIC RESONANCE IMAGING AND POSITRON EMISSION TOMOGRAPHY IN THE PREDICTION OF LEFT VENTRICULAR DYSFUNCTION REVERSIBILITY IN PATIENTS WITH CHRONIC TOTALLY OCCLUDED CORONARY ARTERIES - D. V. Ryzhkova; I. S. Kostina (Российский кардиологический журнал)
Aim. To compare the prognostic value of cardiac positron emission tomography (PET) and contrast-enhanced magnetic resonance imaging (ceMRI) for the prediction of reversibility of regional left ventricular (LV) dysfunction after endovascular recanalization of chronic totally occluded (CTO) coronary arteries (CA). Material and methods. The study included 26 patients with chronic coronary heart disease and angiographically confirmed CTO CA. All participants underwent cardiac ceMRI and PET with 13N-ammonia and 18F-fluorodeoxyglucose (18F-FDG). Successful CTO CA recanalization was achieved in 20 patients. The standard for prognostic value assessment was the improvement of regional LV contractility at the control ceMRI.Results. The values of scar tissue extension and scar tissue volume were significantly higher in the segments with irreversible dysfunction, compared to the respective values for viable myocardium (73,0±37% vs. 20,4±33,7% (p<0,0001) and 54,1±33,4% vs. 9,8±16,2% (p<0,0001), respectively). An opposite tendency was observed for the 18F-FDG uptake (51,8±17% vs. 67±11,6% (p<0,001)). The ROC analysis demonstrated that the maximal cut-off values of scar tissue extension and scar tissue volume, assessed by ceMRI (<50% and <37,5%, respectively), predicted the improvement in the regional LV contractility with sensitivity, specificity, and accuracy of 80,2%, 78%, 79,6%, and 92,7%, 73,2%, and 86,9%, respectively. The minimal cut-off value of >56,4% for the 18F-FDG uptake and the patterns of perfusion-metabolism match/ mismatch provided sensitivity of 81,1% vs. 91%, specificity of 67,5% vs. 65,5%, and accuracy of 75,2% vs. 83,3%, respectively.Conclusion. Compared to cardiac PET ceMRI has superior prognostic value and accuracy in the prediction of reversibility of the regional LV dysfunction after endovascular revascularization of CTO CA. In patients with ceMRI contraindications, a complex PET assessment of myocardial perfusion and metabolism is recommended. PET with F-FDG only is less effective in the prediction of the LV dysfunction reversibility, but can still detect the presence of viable cardiomyocytes in the severely affected myocardial segments.